Engineering an Au nanostar-based liquid phase interfacial ratiometric SERS platform with programmable entropy-driven DNA circuits to detect protein biomarkers in clinical samples. Issue 3 (13th December 2021) - Fan, Guanli; Gao, Xiaorong; Xu, Shuling; Li, Xia; Zhang, Qi; Dai, Caifeng; Xue, Qingwang; Wang, Huaisheng
Abstract : An Au nanostar-based liquid phase interfacial ratiometric SERS platform with programmable entropy-driven DNA circuits was engineered to detect protein biomarkers Mucin 1 (MUC1) in clinical samples with high sensitivity and accuracy. Abstract : Developing sensing platforms that simultaneously integrate high sensitivity and accuracy has been a promising but challenging task for the detection of protein biomarkers in clinical samples. Herein, we engineered an Au nanostar-based liquid phase interfacial ratiometric SERS platform with programmable entropy-driven DNA circuits to detect the protein biomarker Mucin 1 (MUC1) in clinical samples.